Multidomain IT architectures for next-generation communications service providers [Next-Generation Telco IT Architectures] - O'SULLIVAN, DECLAN; BRENNAN, ROB; FEENEY, KEVIN; KEENEY, JOHN (My University, 2010)
Enabling interdomain and end-to-end management are major challenges for IT architectures supporting agile next-generation communications service providers. This requires explicit management of the interdomain relationships themselves rather than treating extradomain resources or services as equivalent to internal capabilities. In this article we describe a general layered model for describing interdomain relationships and a concrete architecture for a domain relationship manager based on a combination of model-driven development and semantic web technology. Our prototyping efforts are discussed, and both examples and descriptions aid gaining an understanding of the underlying technologies. Finally, a use case is presented to illustrate the application of these techniques and especially to show the dynamic behavior of a system based on this engineering approach.
PUBLISHED
Keywords: Telecommunications; Multidomain IT architectures; Intelligent Content & Communications; Telecommunications